An Application of Analytic Hierarchy Process in Vehicle Routing Problem - Balaji, M.; Santhanakrishnan, S.; Dinesh, S. N. (Periodica Polytechnica Transportation Engineering, 2019)
Vehicle Routing Problem (VRP) facilitates on finding a set of trips, one for each vehicle and to deliver known quantities of goods from a single depot to a set of geographically dispersed customers. This paper proposes an effective hybrid approach that combines customer prioritization with the Clarke and Wright's savings algorithm to solve the capacitated vehicle routing problem. In this model, in addition to traditional objective of resolving vehicle routing problem, the customer satisfaction have been taken into account. Initially, all the customers have been clustered with the help of Clarke and Wright's saving algorithm and later the customers have been prioritized on assigning optimal route using Analytic Hierarchy Process (AHP) as a Multi Criteria Decision Making (MCDM) tool. The highlight of this research is to diminish the total transportation cost without violating the vehicle capacity and ultimately improve the customer satisfaction.